(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Social media that is used at all times can attract users’ interest in terms of interest in a trend that exists in society. The rapid spread of information using social media can influence behavior and trends. Therefore there is a shift in marketing, promotion, and advertising. By seeing the potential of large social media users, advertisers and how to market products use a lot of visual media. Social media can be used for various purposes. The rapid progress in the field of information technology is balanced by advances in transportation technology and logistics management. This makes it easier for human and goods traffic. These two things should be business opportunities that must be utilized. In this case, how to utilize social media that is widely used in all circles such as WhatsApp, Instagram, Youtube, TikTok, Facebook Twitter, or others to market products. Local products on a household industry scale have many product variations, but the problem is in introducing local products and not being optimal in packaging and marketing. One of the household industry groups that is a partner is the household industry group in producing processed snack products such as crackers, vegetable chips, and cookies. This activity aims to provide assistance and direct practice in the use of social media to residents to find out how to market with social media and packaging uniquely and attractively. The results of this activity are expected that partners can increase income and knowledge in the use of Information technology.